The Mystery Of The Spiteful Letters - Blyton, Enid (London Egmont / Eurokids International Ltd, 2011)
A fantastic children's crime story from the world's best-loved children's author, Enid Blyton. Pip and Bets' housemaid receives a spiteful letter in the post. Then Mrs Moon receives one too. Who would want to make them so miserable? By piecing together the clues, the Find-Outers are determined to find the culprit. See how they get on in The Mystery of the Spiteful Letters. The Mystery series follows the adventures of 'The Five Find Outers' - Pip, Bets, Larry, Daisy and Fatty, as they solve the most unusual crime cases with the help of their dog Buster. Enid Blyton is arguably the most famous children's author of all time. Thanks to series such as The Wishing-Chair, The Faraway Tree-, The Mysteries, The Famous Five and The Secret Seven, she has sold over 400 million books in more than 40 languages worldwide. Her Mysteries stories have charmed generations of children - and they are as popular today as they have ever been.
Keywords: Children's Literature - Fiction : Detective / Mystery